Dialogue-based visualization for quranic text - Mustapha, Aida (EuroJournals Publishing, 2009)
Visualization is a human cognitive activity and is not something that a computer does. A good visualization for Quranic text enables us to communicate the content with clarity, precision, and efficiency. Being a large information source, a visualization system for Quranic text is required. This paper proposes AQILAH, dialogue-based information visualization for Quranic text. AQILAH facilitates the interaction and rearrange the content based on need-to-know basis, as opposed to sequential order as in recitals.